2019
DOI: 10.1186/s12898-019-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing healthy ecosystems in northern Ghana through eco-friendly farm-based practices: insights from irrigation scheme-types

Abstract: Background Farming practices vary from farmer to farmer and from place to place depending on a number of factors including the agroclimatic condition, infrastructure (e.g. irrigation facilities) and management mechanisms (private versus state management). These together affect the functioning and sustainability of the ecosystems. For the sustainability of ecosystems, farmers need to employ ecosystem-based farm practices. This paper examines the ecosystem-based farm management practices (EBFMPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, practices under Sustainable Land and Water Management include but are not limited to; minimum or no-tillage practices, construction of terraces, soil bunds, stone or vegetation bunds, Half-moons 1 , and Zai pits 2 , mulching, on-farm storage facilities, irrigation, System of Rice Intensification (SRI), and alternate wetting and drying in rice production (Cai et al, 2019;Oremo et al, 2020). Practices aimed at pest and weed management include the use of pesticides, new crop varieties or cultivars that are pest and disease resistant, adoption of push-pull technology, and crop diversification through intercropping or crop rotation (Agula et al, 2019). Other practices include agroforestry and cover cropping, changing of planting dates, index-based insurance, and use of organic manure among others.…”
Section: Introductionmentioning
confidence: 99%
“…For example, practices under Sustainable Land and Water Management include but are not limited to; minimum or no-tillage practices, construction of terraces, soil bunds, stone or vegetation bunds, Half-moons 1 , and Zai pits 2 , mulching, on-farm storage facilities, irrigation, System of Rice Intensification (SRI), and alternate wetting and drying in rice production (Cai et al, 2019;Oremo et al, 2020). Practices aimed at pest and weed management include the use of pesticides, new crop varieties or cultivars that are pest and disease resistant, adoption of push-pull technology, and crop diversification through intercropping or crop rotation (Agula et al, 2019). Other practices include agroforestry and cover cropping, changing of planting dates, index-based insurance, and use of organic manure among others.…”
Section: Introductionmentioning
confidence: 99%
“…The provision of irrigation facilities in strategic locations in rural areas, especially in northern Ghana, is expected to help promote livelihoods in those areas [4][5][6][7]. This is because it has been established in the empirical literature that access to irrigation has positive impacts on agricultural production and the reduction of poverty levels of farmers [8].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, other studies in Uganda [34] and in Nigeria [4] found the oppositethat larger households featured higher adoption intensity. Concerning marital status, explored in studies in Africa, it was found that in Nigeria single farmers were more likely to adopt organic farming technology than married farmers [3], but in Ghana married farmers were willing to pay more for sustaining ecosystem-based farm management practices than those not married [7].…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Farmers' assessment of plot characteristics in terms of fertility, slope, and depth was found to be among the factors influencing adoption of sustainable intensification practices in Kenya [35], Malawi [11], Thailand [51], Ethiopia [2], USA [27], Malaysia [48], and China [47]. In Ghana [6,7] farmers who considered their farmlands to be fertile were willing to pay more to sustain ecosystem-based farm management practices than those who considered their lands to be less fertile. At the same time, a study in the USA [18] focusing on cover crops and no-till/reduced tillage found that the physical features of the farmland, such as soil types, drainage, and/or topography, were only slightly limiting their adoption.…”
Section: Environmental Conditionsmentioning
confidence: 99%